Juridical analysis of legal protection for online fintech debtors “Cash Maju” - Monica Maya Franscisca; Sari Mandiana; Andyna Susiawati Achmad (Trigin Publisher, 2023)
Cash Maju is one of the Fintech Lending Applications that offers accounts receivable online. In the implementation of online accounts receivable practices, it should be in accordance with the provisions of POJK Number 10 of 2022. Data collection is carried out by researching library materials or secondary materials. The approach taken is through the Law (statute approach) by examining each related Law and regulation, and through a conceptual approach, which is an approach carried out by looking at the doctrines of legal experts contained in the literature. The results of the analysis of this final project show that the establishment of online loans should obtain a business license from the OJK in accordance with the provisions of Article 8 of POJK Number 10 of 2022. Cash Maju is an illegal lending and borrowing application and can be subject to PMH in Article 1365 of the Civil Code. The agreement between Cash Maju and debtor Asep Sunandar is an invalid agreement because it violates the fourth condition of 1320 of the Civil Code. Cash Maju's action of disseminating Asep Sunandar's personal data is defamation as stated in Article 27 of the ITE Law so that Asep Sunandar gets legal protection from the ITE Law.